The evolution of competition law in New Zealand - Ahdar, Rex J. (Oxford : Oxford University Press, 2020)
As a compact, liberal, industrialized democracy, 1980s New Zealand proved a useful place to try out the latest fads in market deregulation. This title presents a comprehensive chronicle and critical analysis of how well New Zealand's competition law fared in combatting mergers, monopolies, and cartels.
This edition also issued in print: 2020.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on August 25, 2020).
Keywords: Competition, Unfair -- New Zealand; Antitrust law -- New Zealand